Patients as team members: Factors affecting involvement in treatment decisions from the perspective of patients with a chronic condition - Martina Buljac‐Samardzic; Mark A. Clark; N. Job. A. vanExel; Jeroen D. H. vanWijngaarden (Wiley, 2022)
Abstract Background Active patient involvement in treatment decisions is seen as a feature of patient‐centred care that will ultimately lead to better healthcare services and patient outcomes. Although many factors have been identified that influence patient involvement in treatment decisions, little is known about the different views that patients have on which factors are most important. Objective This study explores the views of patients with a chronic condition on factors influencing their involvement in treatment decisions. Design Q‐methodology was used to study the views of patients. Respondents were asked to rank a set of 42 statements from the least important to the most important for active patient involvement in treatment decision‐making. The set of 42 statements was developed based on a literature search and a pilot in which two external researchers, 15 patients and four healthcare professionals participated. A total of 136 patients with one of three major chronic conditions were included: diabetes types 1 and 2, respiratory disease (i.e., chronic obstructive pulmonary disease and asthma) and cancer (i.e., breast cancer and prostate cancer). Data were collected in a face‐to‐face interview setting in the Netherlands. Results Four distinct views on the factors influencing active patient involvement were identified among patients with a chronic condition. (1) Enabled involvement: the extent to which patients are facilitated and empowered to participate will lead to patient involvement. (2) Relationship‐driven involvement: the relationship between patients and healthcare professionals drives patient involvement. (3) Disease impact‐driven involvement: the severity of disease drives patient involvement. (4) Cognition‐driven involvement: knowledge and information drive patient involvement. Discussion and Conclusion From the patients' perspective, this study shows that there is no one‐size‐fits‐all approach to involving patients more actively in their healthcare journey. Strategies aiming to enhance active patient involvement among patients with a chronic condition should consider this diversity in perspectives among these patients. Patient Contribution Patients are the respondents as this study researches their perspective on factors influencing patient involvement. In addition, patients were involved in pilot‐testing the statement set.